Noticieros radiales. Análisis comparativo de los segmentos de noticias de Radio Life y Radio Libre en el 2023 - Maldonado Correa, Mildred Angely (2023)
The present case study was in charge of carrying out a comparative analysis of the news segments of Radio Life and Radio Libre, in which the diversity of existing communication media in society allows the freedom to use according to the needs, however, the radio It is without a doubt a well-known and preferred means of mass communication by a large part of the population. The problem damaged in the present investigation covers the little informative content that is broadcast on the radios of the city of Babahoyo, which causes the misinformation of the society that prefers to be informed by said media. The methods used in the investigation were the interviews and the observation sheets, obtaining as results to clarify that in both web portals the news information duly updated to date is not found, which causes some disagreement towards the audience that listens to them, for its part Radio Libre on its website has a section to tune in to its live frequency, while Radio Life does not handle this type of section on said site.